Evaluation of Thematic Integrative Learning Programs in Elementary School YPS Pertamina Prabumulih - Nagara, Khaerul Budhy; Tola, Burhanudin; Suprayati, Yetti (International Journal for Educational and Vocational Studies, 2020)
The aims of this research is to evaluate the integrative thematic learning : 1). The context component is the environment conditions that support learning, 2). The input component is the school facilities and human resources, 3). The process component is the   process of planning and implementing of integrative thematic learning, and 4). The product component is the  learning result of  the students. This  research is evaluation  research. The sources of this research are the primary one students of YPS Pertamina Prabumulih School Palembang. The data was collected by observation, quitionare, test and documentation then analyzed as a quantitative descriptive. The conclusions of this research are: (1) The component of context is good in sub component of the condition school environment and the sub component of the psichologic condition school member, 2). The component of input is good in the sub component of school fasilities and human resources, 3) The component of process is good in sub component of planning and implementing integrative thematic learning, and 4). The component of product is good in the learning results of students.